2020
DOI: 10.1016/j.xcrm.2020.100158
|View full text |Cite
|
Sign up to set email alerts
|

ACCELERATE: A Patient-Powered Natural History Study Design Enabling Clinical and Therapeutic Discoveries in a Rare Disorder

Abstract: Summary Geographically dispersed patients, inconsistent treatment tracking, and limited infrastructure slow research for many orphan diseases. We assess the feasibility of a patient-powered study design to overcome these challenges for Castleman disease, a rare hematologic disorder. Here, we report initial results from the ACCELERATE natural history registry. ACCELERATE includes a traditional physician-reported arm and a patient-powered arm, which enables patients to directly contribute medical data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…Any patient who has received a pathology report suggestive of Castleman disease can self‐enroll in the natural history registry. Previously, it was reported that ACCELERATE is skewed towards more symptomatic and less easily treated patients, who are more likely to seek out resources online 26 . Accordingly, ACCELERATE is likely biased towards a higher iMCD‐TAFRO population than the general iMCD population, as these patients typically have a more severe and unpredictable clinical course and may be more likely to seek out resources.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Any patient who has received a pathology report suggestive of Castleman disease can self‐enroll in the natural history registry. Previously, it was reported that ACCELERATE is skewed towards more symptomatic and less easily treated patients, who are more likely to seek out resources online 26 . Accordingly, ACCELERATE is likely biased towards a higher iMCD‐TAFRO population than the general iMCD population, as these patients typically have a more severe and unpredictable clinical course and may be more likely to seek out resources.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was reported that ACCELERATE is skewed towards more symptomatic and less easily treated patients, who are more likely to seek out resources online. 26 Accordingly, ACCELERATE is likely biased towards a higher iMCD-TAFRO population than the general iMCD population, as these patients typically have a more…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a paucity of data describing the natural history of all forms of CD and limited data related to outcomes and prognosis 4,26 . ACCELERATE is an international natural history registry established in 2016 to collect real‐world data on patients with CD 20,27 . Patients who have received a pathological CD diagnosis can enrol online (http://www.cdcn.org/ACCELERATE) from anywhere in the world or through one of nine sites in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…Diagnostic lymph node samples were obtained from iMCD patients enrolled in the ACCELERATE Natural History Registry (NCT02817997). 17 All subjects gave written informed consent, and the studies were approved by local institutional review boards in accordance with the provision of the Declaration of Helsinki and Good Clinical Practice Guidelines. Tissue from eight iMCD‐NOS and eight iMCD‐TAFRO patients was procured following formalin‐fixation paraffin embedding (FFPE).…”
Section: Methodsmentioning
confidence: 99%